(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
This study explores how different values of frequencies of harmonic dynamic load affect the vertical displacement of soils located directly underneath the foundation. A wide range of frequencies (1 – 50 Hz was selected in this study, in addition to four types of sandy soil underneath the foundation: loose, medium, dense and very dense with modulus of elasticity, E of 7000, 19000, 36000 and 70000 kN/m2 respectively. Each type of soil was subjected to three levels of distributed dynamic stresses named 100, 200 and 300 kN/m2. The simulation was carried out theoretically using a two-dimensional software finite element model (FEM) in PLAXIS 2-D package. Two models were used to simulate the soil: elastic and Mohr–Coulomb (M-C) models. The results showed that the vertical displacement underneath the foundation decreases with increasing the load frequency for all types of sandy soil investigated in this study and for all values of dynamic load. There is a sharp drop in vertical displacement when the load frequency increased from 1to 10 Hz. The vertical displacement remains constant regardless the value of dynamic load when the load frequency exceeds 30 Hz. Finally, the drop in vertical displacement at first parts of curves (frequency from 1 to 10 Hz.) is sharper in loose sand compared with other types of sandy soil i.e. medium, dense and very dense.